Social support, Quality of life, and Death Anxiety among Soldiers in Papua - Xavier, Selyo Febrio; Rini, Rr. Amanda Pasca; Ariyanto, Eko April (Universitas Negeri Surabaya, 2025)
Background: Soldiers in conflict areas face heightened death anxiety due to physical challenges, armed conflict, and harsh conditions. Social support and quality of life are vital for their psychological well-being. Objective: To examine the role of quality of life as a mediator between social support and death anxiety among Indonesian National Armed Forces in Papua. Method: Correlational quantitative research involving 165 samples using the accidental sampling technique. Measurement using scales of death anxiety, social support, and quality of life. Path analysis was used to analyze the data. Results: The findings indicate a significant negative relationship between social support and death anxiety (r = -0.421, p < 0.001), as well as a significant positive relationship between social support and quality of life (r = 0.536, p < 0.001). There is a significant negative relationship between quality of life and death anxiety (r = -0.478, p < 0.001), which also acts as a mediator. Conclusion: Social support can improve the quality of life and reduce death anxiety among Indonesian National Armed Forces in Papua. This study suggests psychosocial interventions to improve soldiers' psychological well-being through enhancing social support and quality of life. Keywords: Death anxiety; military personnel; Papua; quality of life; social support. Abstrak Latar Belakang: Tugas prajurit di daerah konflik meningkatkan kecemasan terhadap kematian akibat tantangan fisik, konflik bersenjata, dan kondisi geografis yang sulit. Dukungan sosial serta kualitas hidup prajurit berperan penting dalam kesejahteraan psikologis mereka. Tujuan: Untuk menguji peran kualitas hidup sebagai mediator antara dukungan sosial dan kecemasan kematian pada prajurit TNI di Papua. Metode: Penelitian kuantitatif korelasional dengan melibatkan 165 sampel dipilih menggunakan teknik accidental sampling. Pengukuran dengan skala kecemasan terhadap kematian, dukungan sosial, dan kualitas hidup. Analisis jalur digunakan untuk menganalisis data. Hasil: Temuan menunjukkan hubungan negatif signifikan antara dukungan sosial dengan kecemasan kematian (r = -0,421, p < 0,001), serta hubungan positif signifikan antara dukungan sosial dengan kualitas hidup (r = 0,536, p < 0,001). Hubungan negatif signifikan antara kualitas hidup dengan kecemasan kematian (r = -0,478, p < 0,001), sekaligus berperan sebagai mediator. Simpulan: Dukungan sosial yang kuat dapat meningkatkan kualitas hidup dan mengurangi kecemasan terhadap kematian pada prajurit TNI di Papua. Penelitian ini menyarankan intervensi psikososial untuk meningkatkan kesejahteraan psikologis prajurit melalui penguatan dukungan sosial dan kualitas hidup. Kata Kunci: Dukungan sosial; kualitas hidup; kecemasan kematian; Papua, prajurit militer.